COLLABORATIVE WRITING AND CRITICAL THINKING - Murnijati, _ (2016)
This study aims to investigate the elements of critical thinking (CT) demonstrated in students' writing resulted from collaborative writing, and how collaborative writing (CW) helps develop students' critical thinking. The study involved 27 Grade XII students, an observer, and the researcher as the participant observer who conducted the teaching program in her regular class. The study employed the qualitative case study approach which obtained the data from students' writing texts, classroom observation, and student interview. The CT elements as well as the CT dispositions were analysed based on the CT theories proposed mainly by Reichenbach, Chaffee, Ennis, Browne and Keeley. Findings revealed that the students were able to demostrate the CT elements namely issue, arguments, facts, and opinions in their writing. In general, their arguments did not satisfy the expected standards of clarity, sufficiency, and accuracy, thus they were weak or unsound. However, during the CW process, the students demonstrated CT dispositions through their attempts as typically critical thinkers do. From the teaching program, it was obvious that CW with the heterogeneous groups, the well-organized writing phases, the writing task, and the teacher's role as a facilitator, motivator, and a model of CT dispositions, had provided large spaces for students to engage actively in meaningful interactions that encouraged them to use their thinking. To ensure validity, triangulation was conducted by student interviews. Findings suggest that students need to be habituated to the learning involving CT, and given guidance to improve the quality of their writing and thinking. Meanwhile, the teacher needs to improve her teaching of writing and CT explicitely through ELT in the future.